Comparative assessment of the respiratory function of young and skilled archers at the stage of pre-competition training - Tarasova, L. V.; Tarasov, P. Yu.; Gombozhapova, Kh.-Ts. D.; Sapunov, V. N.; Pankov, V. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The paper presents a comparative analysis of the functional parameters of the respiratory system of young and skilled archers in the process of their pre-competitive training. The participants are elite athletes (n = 13) and juniors (n = 11). The most important indicators have been highlighted, reflecting the preparedness of athletes and ensuring the effectiveness of the training process during the pre-competition training. The most informative factors are indicators of the respiratory function and the functional state of the respiratory system: Excursion of the chest, expiratory respiration rate, Genchi test, lung capacity and proper lung capacity. The obtained data can be used in assessing preparedness in the framework of qualifying competitions.